2006
DOI: 10.1183/09031936.00073606
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT screening of asbestos-exposed workers: lung lesions and incidental findings

Abstract: The objective of the present study is to determine the feasibility of chest computed tomography (CT) in screening for lung cancer among asbestos-exposed workers.In total, 633 workers were included in the present study and were examined with chest radiography and high-resolution CT (HRCT). A total of 180 current and ex-smokers (cessation within the previous 10 yrs) were also screened with spiral CT. Noncalcified lung nodules were considered positive findings. The incidental CT findings not related to asbestos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 32 publications
2
47
0
2
Order By: Relevance
“…From 2002 to 2009, the results of some lung cancer screening trials with LDCT on asbestos-exposed workers were published (29)(30)(31)(32)(33)(34). Unfortunately, in these studies CT image acquisition and reconstruction algorithms are different as well as technical parameters (mA, slice thickness, reconstruction interval, additional HRCT slices, etc.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2002 to 2009, the results of some lung cancer screening trials with LDCT on asbestos-exposed workers were published (29)(30)(31)(32)(33)(34). Unfortunately, in these studies CT image acquisition and reconstruction algorithms are different as well as technical parameters (mA, slice thickness, reconstruction interval, additional HRCT slices, etc.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 99%
“…); furthermore, the criteria to determine a positive test are not homogeneous. Most of all use ELCAP, I-ELCAP criteria (22,23) or a modification of these (29,31,32,35) to determine a positive test for non-calcific nodule; in other trials the presence of pleural abnormalities is a criterion considered for a positive test (29)(30)(31)(32), but the definitions of pleural involvement and subsequent work-up are various and not always included in the protocol study.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 99%
“…The first study group (n5602) was recruited in 1996-1997 and consisted of asbestos-exposed subjects who lived in the Helsinki (Finland) area, and had an asbestos-related occupational disease and a smoking history [22,23]. The second study group (n5633) was recruited in [2003][2004], and consisted of asbestos-exposed persons from three geographic areas (Helsinki, Tampere and Turku, Finland) who were heavily exposed, had previously been diagnosed with asbestos-related occupational disease, or had visited occupational medicine clinics in Helsinki and Tampere for clinical follow-up [24].…”
Section: Study Populationmentioning
confidence: 99%
“…A recent paper showed that cancers found in such screening have a favourable prognosis [1]. One of the major limitations of CT screening is the large number of non-specific lung nodules, ranging from 6.7 % or 14 % [2][3][4] in baseline screening up to 74 % among those repeatedly screened [5]. These findings cause a great burden, because their benign nature has to be confirmed with extra studies.…”
Section: Introductionmentioning
confidence: 99%